2017
DOI: 10.1016/j.athoracsur.2016.05.098
|View full text |Cite
|
Sign up to set email alerts
|

An Expansible Aortic Ring in Aortic Root Remodeling: Exact Position, Pulsatility, Effectiveness, and Stability in Three-Dimensional CT Study

Abstract: This study demonstrates imaging evidence of the effectiveness, stability, and pulsatility of the annuloplasty ring in aortic root remodeling in follow-up and describes the exact position of the ring at the base of the aortic root.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The two most commonly used annuloplasty techniques for aortic valve repair is the Dacron ring annuloplasty obtained from Dacron tube grafts (Vascutek, Terumo, Japan) and the polytetrafluoroethylene (PTFE) suture annuloplasty. Both annuloplasties have shown good results with or without the remodeling procedure (8)(9)(10)(11). However, some concerns have been raised regarding the expansibility of the Dacron ring annuloplasty throughout the cardiac cycle, because the material of the Dacron tube graft is less compliant than the native tissue and is thought to have limited radial expansion capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The two most commonly used annuloplasty techniques for aortic valve repair is the Dacron ring annuloplasty obtained from Dacron tube grafts (Vascutek, Terumo, Japan) and the polytetrafluoroethylene (PTFE) suture annuloplasty. Both annuloplasties have shown good results with or without the remodeling procedure (8)(9)(10)(11). However, some concerns have been raised regarding the expansibility of the Dacron ring annuloplasty throughout the cardiac cycle, because the material of the Dacron tube graft is less compliant than the native tissue and is thought to have limited radial expansion capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Improved repair stability has been reported with the use of this technique in isolated BAV repair [ 2 ]. However, a study using CT imaging revealed that the Lansac ring was still partially above the VBR, especially at the level of the commissure between the left and right coronary sinuses in the tricuspid aortic valve non-functional commissure in type 1 R/L BAV and at the level of the right coronary sinus [ 28 ]. According to de Kerchove et al .…”
Section: Discussionmentioning
confidence: 99%
“…We thank Yurekli and colleagues [1] for their letter on our article titled "An Expansible Aortic Ring in Aortic Root Remodeling: Exact Position, Pulsatility, Effectiveness, and Stability in Three-Dimensional CT Study" [2].…”
Section: Reply To the Editormentioning
confidence: 99%